WATERBASED PVDF SLURRY FORMULATION FOR SILICON GRAPHITE ANODES - HE, Wensheng; BONNET, Anthony; FINE, Thomas; FUKUYAMA, Takehiro (2021)
The invention relates to a silicon graphite anode comprising an aqueous binder, to its method of preparation and to its use in a Li-ion battery. Another subject matter of the invention is the Li-ion batteries manufactured by incorporating this electrode material. L'invention concerne une anode en graphite-silicium comprenant un liant aqueux, son procédé de préparation et son utilisation dans une batterie Li-ion. L'invention a également pour objet les batteries Li-ion fabriquées par incorporation de ce matériau d'électrode.